AB0648 Anticentromere Antibodies: Clinical Significance in A Large Cohort of Patients with A Long Follow-Up. (15th July 2016) - Alende, V.; González, E.; Vázquez-Triñanes, C.; González, L.; Lorenzo, A.; Villaverde, I.; Alonso, M.; Rodríguez, S.; Isorna, M.J.; Eiras, P.; Sopeña, B.; ,
Abstract : Background: The presence of anti-centromere antibodies (ACA) has been associated with limited cutaneous systemic sclerosis (lcSSc), primary biliary cirrhosis (PBC), Sjogren's syndrome and less frequently with other autoimmune diseases (AID). However, given the low prevalence of ACA (<3% of positive ANA), the series published to date have included few patients and with little follow-up, so there have been mixed results (1, 2). Objectives: The aim of the study was to establish the clinical significance of ACA in a large group of patients with a long follow-up. Methods: The study was conducted at six affiliated University hospitals on all patients with positive ACA by indirect immunofluorescence on Hep-2 cells, between January 2011 and December 2014. Subsequently, the date of the first positive determination to ACA was identified in the patient's electronic file. Low titers of ACA were considered when the highest value was 1/320. Only those who have 2 or more positive determinations were included. All laboratory tests, echocardiography, CT of the chest and the final diagnosis were carefully reviewed. Results: A total of 308 patients were studied, 269 were women (87%). The mean age was 70.21±13.5. The mean follow-up from the first determination of positive ACA was 125.43 months (range 11–276). High titers of ACA (>1/1280) were recorded in 94.5% of patients. The ACA was the only positive antibody in 219 patients (71.1%). On the other patients the associated antibodies were: AMA 15%, anti-Ro 6%, ASMA 2.2%, anti-Scl 70 1.5% and anti-gastric parietal cell in 2.9%. Regarding the diseases diagnosed in ACA patients: 57% had systemic sclerosis most of them lcSSc, 11% PBC, 6.6% Raynaud without systemic manifestations, 3% Sjogren's syndrome, 3% Arthritis, 2% Autoimmune hepatitis (AIH). Also, there was a 5.9% (17 patients) with overlap syndromes (lcSSc + PBC; AIH + PBC; AIH + Rheumatoid arthritis). Of the 175 patients with lcSSc 16% had pulmonary arterial hypertension, 10% interstitial lung disease and 5% suffered from digital ulcers. No autoimmune disease was diagnosed during the follow-up in 65 patients (21%). Among the 14 patients with low titers of ACA only 28.6% had AID. Conclusions: The presence of anticentromere antibodies were associated with a high likelihood of developing anautoimmune dise ase (80%) mainly limited cutaneous systemic sclerosis, so these patients should be adequately evaluated and followed. However, low titers of ACA decrease the frequency of associated autoimmune diseases. References: Miyawaki S, Asanuma H, NishiyamaS, Yoshinaga Y. Clinical and serological heterogeneity in patients with anticentromere antibodies. J. Rheumatol 2005; 32:1488–94. Incidence and clinical correlation of anticentromere antibody in Thai patients. Clin Rheumatol 2006; 25:325–8 Disclosure of Interest: None declared